2021
DOI: 10.3389/fmed.2021.664023
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Generalizability of Infantile Cataracts Detection via Deep Learning-Based Lens Partition Strategy and Multicenter Datasets

Abstract: Infantile cataract is the main cause of infant blindness worldwide. Although previous studies developed artificial intelligence (AI) diagnostic systems for detecting infantile cataracts in a single center, its generalizability is not ideal because of the complicated noises and heterogeneity of multicenter slit-lamp images, which impedes the application of these AI systems in real-world clinics. In this study, we developed two lens partition strategies (LPSs) based on deep learning Faster R-CNN and Hough transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…DVA, or dynamic visual acuity, refers to the ability to capture, decompose, and perceive images of moving objects while observing (Jiang et al, 2021 ). For high-altitude flight, pilots must constantly observe the display and control interfaces and the external environment in a relatively non-stationary state in order to rapidly and accurately obtain real-time information related to flight safety, which is crucial to ensure the stable operation of the aircraft.…”
Section: Discussionmentioning
confidence: 99%
“…DVA, or dynamic visual acuity, refers to the ability to capture, decompose, and perceive images of moving objects while observing (Jiang et al, 2021 ). For high-altitude flight, pilots must constantly observe the display and control interfaces and the external environment in a relatively non-stationary state in order to rapidly and accurately obtain real-time information related to flight safety, which is crucial to ensure the stable operation of the aircraft.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al 16 demonstrated robust performance in cataract diagnostic AI using slit-lamp photographs with equal outcomes for ophthalmologists, with a sensitivity and specificity of 92.00% and 83.85%, respectively (Table 1 ). Jiang et al 22 introduced a deep learning-based lens partition model, employing multicenter datasets, which yielded accuracy, sensitivity, and specificity rates ranging from 92.57 to 97.96%, 91.95–97.04%, and 93.08–98.74%, respectively (Table 1 ). Focusing of different disease, Li et al 15 revealed a high performance in the keratitis diagnostic AI model slit-lamp and smartphone photograph (sensitivity: 81.5–98.7%, specificity: 95.0–99.8%, and accuracy: 95.4–99.3%).…”
Section: Discussionmentioning
confidence: 99%
“…This model has the ability to transform cataracts on the basis of monitoring and computation of the intraocular lens (IOL). Jiang et al [18] proposed the Hough transform and R-CNN to improve the generalization of IC (Infantile Cataracts) diagnosis. There were 1643 slit-lamp images were collected from five ophthalmic clinics and they were calculated using the LPS (lens partition strategies).…”
Section: Related Workmentioning
confidence: 99%